Uridine Diphosphate Glucose Metabolism and Callose Synthesis in Cultured Pollen Tubes of Nicotiana alata Link et Otto. - Schlupmann, H. (1994)
Membrane preparations from cultured pollen tubes of Nicotiana alata Link et Otto contain a Ca2+ -independent (1-3)-[beta]-D-glucan (callose) synthase activity that has a low affinity for UDP-glucose, even when activated by treatment with trypsin (H. Schlupmann, A. Basic, S.M. Read [1993] Planta 191: 470-481). Therefore, we investigated whether UDP-glucose was a likely substrate for callose synthesis in actively growing pollen tubes. Deposition of (1-3)-[beta]-glucan occurred at a constant rate, 1.4 to 1.7 nmol glucose min-1, in tubes from 1 mg of pollen from 3 h after germination; however, the rate of incorporation of radioactivity from exogenous [14C]-sucrose into wall polymers was not constant, but increased until at least 8 h after germination, probably due to decreasing use of internal reserves. UDP-glucose was a prominent ultraviolet-absorbing metabolite in pollen-tube extracts, with 1.6 nmol present in tubes from 1 mg of pollen, giving a calculated cytoplasmic concentration of approximately 3.5 mM. Radioactivity from [14C]-sucrose was rapidly incorporated into sugar monophosphates and UDP-glucose by the growing tubes, consistent with a turnover time for UDP-glucose of less than 1 min; the specific radioactivity of extracted UDP-[14C]glucose was equal to that calculated from the rate of incorporation of [14C]sucrose into wall glucans. Large amounts of less metabolically active neutral sugars were also present. The rate of synthesis of (1-3)-[beta]-glucan by nontrypsin-treated pollen-tube membrane preparations incubated with 3.5 mM UDP-glucose and a [beta]-glucoside activator was slightly greater than the rate of deposition of (1-3)-[beta]-glucan by intact pollen tubes. These data are used to assess the physiological significance of proteolytic activation of pollen-tube callose synthase.